PENGARUH PRICE DISCOUNT DAN BONUS PACK TERHADAP IMPULSE BUYING PRODUCT CONVENIENCE GOODS PADA MASA PANDEMI COVID ‘19: PENGARUH PRICE DISCOUNT DAN BONUS PACK TERHADAP IMPULSE BUYING PRODUCT CONVENIENCE GOODS PADA MASA PANDEMI COVID ‘19 - Restanti, Yani Dwi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
This study uses an explanatory research type with associative research specifications. With descriptive inferential quantitative data analysis, it aims to determine the effect of price discounts and bonus packs on impulse buying of convenience goods products for Hypermart Kediri customers in Partial and Simultaneous. Sampling by purposive sampling, data analysis technique using multiple linear regression. The statistical results show that the discount price has an influence on impulse buying for Hypermart customers with a significance value of 0.003 and a regression coefficient of 0.186. The bonus pack has an effect on impulse buying, with a significance value of 0.000 and a regression coefficient of 0.709. Price discount and bonus pack simultaneously affect the impulse buying of convenience goods products for Hypermart Kediri customers, with a significance of 0.000. The results of multiple regression statistics show that the bonus pack has a dominant influence on impulse buying of convenience goods products, this is indicated by the value of 0.714 with a significance value of 0.000. Keywords: pandemic, price discount, bonus pack, impulse buying, behavior change, sales promotion